2002
DOI: 10.1136/bjo.86.9.988
|View full text |Cite
|
Sign up to set email alerts
|

Systemic cyclosporin A in high failure risk, repeated corneal transplantation

Abstract: Systemic cyclosporin A has a limited beneficial effect in preventing immune graft rejection in repeated corneal transplants in a highly vascularised corneal bed. When immune graft rejection occurs in such regrafts, the prognosis is poor despite aggressive medical treatment. Causes other than immune regraft rejection may also result in poor visual outcome in patients with clear regrafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 21 publications
0
35
0
Order By: Relevance
“…However the results are inconsistent. Some studies have demonstrated a beneficial effect, whereas others have failed to find any improvement in outcome [4][5][6][7][8][9]. Mainly because of its nephrotoxic effects, CsA has not become routine in clinical practise.…”
Section: Introductionmentioning
confidence: 92%
“…However the results are inconsistent. Some studies have demonstrated a beneficial effect, whereas others have failed to find any improvement in outcome [4][5][6][7][8][9]. Mainly because of its nephrotoxic effects, CsA has not become routine in clinical practise.…”
Section: Introductionmentioning
confidence: 92%
“…16) Current cyclosporine eye drops developed for clinical application were normally prepared with maize, castor or peanut oil, and the oil-based eye drops were likely to induce side effects including hyperaemia, blurred vision, pricking, burning sensation and pain in the eyes. 17) It is also reported that 2% oil based eye drop would possibly lead to corneal epithelial lesions. 9) To circumvent the drawbacks, we developed cyclosporine eye drops that were produced with nanophase materials.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic administration of CyA is an effective therapy for the corneal graft rejection and some eye disorders. However, the long term systemic administration of a relatively high dose of CyA may lead to the serious systemic adverse effects, such as hypertension, nephrotoxicity and hepatotoxicity (Algros et al, 2002;Rumelt et al, 2002). Topical ocular administration of CyA provides a good alternative to the systemic delivery.…”
Section: Introductionmentioning
confidence: 99%